A Study on the Epectiveness of Health and Wellness Program in Reducing Employee Turnover at Reliance Retail - Thakur, Sangita Anil; Tekade, Atul B. (Journal of Neonatal Surgery, 2025)
Employee turnover remains a significant challenge for organizations, affecting productivity, operational costs, and workplace morale. Health and wellness programs have emerged as strategic tools aimed at fostering employee well-being and reducing attrition rates. This study examines the effectiveness of health and wellness initiatives in mitigating employee turnover at Reliance Retail. A structured analysis explores the direct and indirect impacts of such programs on job satisfaction, work-life balance, and overall engagement. Data collection involves a combination of surveys and interviews conducted among employees at various levels, assessing their perspectives on the accessibility, utilization, and benefits of wellness initiatives. Findings indicate that organizations investing in comprehensive wellness programs experience a noticeable decline in voluntary turnover, as employees feel valued and supported. Additionally, factors such as stress management, physical fitness initiatives, and mental health support play a crucial role in enhancing employee retention. The study further highlights that companies integrating holistic wellness strategies witness improved workforce morale and productivity. A well-structured health and wellness program does not merely contribute to physical well-being but also fosters a positive organizational culture, strengthening employer-employee relationships. The research provides insights into how Reliance Retail’s wellness initiatives impact employee loyalty and performance, offering recommendations for optimizing such programs to maximize retention. Future studies can explore the long-term financial benefits of wellness programs in reducing hiring and training costs associated with high attrition. By adopting data-driven wellness strategies, businesses can enhance employee engagement, mitigate workplace stress, and ensure sustainable workforce stability in the dynamic retail sector..